Are labor unions important for business cycle fluctuations? Lessons from Bulgaria - Aleksandar Vasilev (Eurasian Economic Review, 2019)
In this paper we investigate the quantitative importance of collective bargaining agreements for the observed fluctuations in Bulgarian labor markets. Following Maffezzoli (2001), we introduce a monopoly union into a real-business-cycle model with government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018), and compare and contrast it to a model without unions. We fi nd that the sequential bargaining procedure between the monopoly union and the stand-in rm produces an important internal propagation mechanism within the theoretical setup, which allows the monopoly model to fi t data better than the alternative framework with perfectly-competitive labor markets.
Keywords: E24; E32; J23; J51; 330; business cycles; general equilibrium; labor unions; indivisible labor; involuntary unemployment